2016
DOI: 10.1155/2016/5141089
|View full text |Cite
|
Sign up to set email alerts
|

GC Gene Polymorphisms and Vitamin D-Binding Protein Levels Are Related to the Risk of Generalized Aggressive Periodontitis

Abstract: Objective. To explore whether GC (group-specific component) rs17467825, rs4588, and rs7041 polymorphisms are associated with generalized aggressive periodontitis. Methods. This case-control study recruited 372 patients with generalized aggressive periodontitis (group AgP) and 133 periodontal healthy subjects (group HP). GC rs17467825, rs4588, and rs7041 genotypes and plasmatic vitamin D-binding protein (DBP) were measured. Analysis of single SNP and multiple SNPs was performed and relevance between plasmatic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…We confirmed the role of rs4588 and found a non-significant association between rs7041 and DBP levels. [30,31] We also report statistically significant associations between rs17467825 and rs2209314 and DBP levels. Rs17467825 is located in the 3′-UTR region of the GC gene and is in strong linkage disequilibrium with causal functional variants affecting the mRNA stability of DBP [32].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…We confirmed the role of rs4588 and found a non-significant association between rs7041 and DBP levels. [30,31] We also report statistically significant associations between rs17467825 and rs2209314 and DBP levels. Rs17467825 is located in the 3′-UTR region of the GC gene and is in strong linkage disequilibrium with causal functional variants affecting the mRNA stability of DBP [32].…”
Section: Discussionsupporting
confidence: 55%
“…Rs17467825 is located in the 3′-UTR region of the GC gene and is in strong linkage disequilibrium with causal functional variants affecting the mRNA stability of DBP [32]. Song W. et al reported that this SNP is in a haplotype block with rs7041 and rs4588 and affected DBP levels in a periodontitis patient group [31].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have linked increased levels of vitamin D with minimizing tooth loss resulting from periodontitis [90,91,92,93,94,95,96]. Additionally, vitamin D receptor polymorphisms [97] and for vitamin D binding protein appear to have some impact on increasing the risk for periodontitis [98,99]. Research has also found that patients with low serum vitamin D levels, exhibited healing from periodontal surgery was adversely affected [100].…”
Section: Discussionmentioning
confidence: 99%
“…Table summarizes the results derived from 22 studies. In total, 30 loci and genes were identified in which one or several genetic variants were associated with AgP (Table ) . Studies were based either on candidate‐gene approach (CGA) or genome‐wide association studies (GWAS) (Table ).…”
Section: Literature Reviewmentioning
confidence: 99%